Diagnosis of the prevailing status of the evaluative proposals in a course according to the theorical-methodological setting of assess to learn. Experience systematization (Revista Electrónica Calidad en la Educación Superior, 2018)
A systematization of an experience was done within the teaching and learning process of UNED Costa Rica, which is included in its Academical plan 2012-2017 for the subject called New product development Seminar II. This is part of the Agro industrial Engineering career. Nine criteria given by the knowledge Evaluation and curricular support Program of UNED were used to determine dissatisfactions in terms of evaluation and two main cathegories were found: the level of participation of the actors in the learning and evaluation process as well as the inherent characteristics of the formative function. An active participation from students and teachers was observed during the implementation, as well as a more conscious way of handling each evaluative activity and instrument. It is recommended to use this new methodology in other subjects to improve quality and performance of students.